Empowerment of Women Through Self Help Group - Sreeramulu,G (Kalpaz Publications, 2006)
The book is an in-depth study of 'Empowerment of Women Through Self Help Groups. It covers the problems and perspectives of Self Help Groups and suggest several measures. The study has evaluated the implementation of several schemes in Anantapur District in particular and in Andhra Pradesh in general such as rearing goats, dairying, petty business activities, making of soft toys and so on. The findings are very much encouraging, such as Women are now managing their families, Panchayat Raj Institutions, are able to concentrate on their children's education and health. Contents include: Introduction, Public Policy Theoretical Perspectives, Evaluation, Aims and Objectctives of Self Help Groups in Anantapur District, Socio-Economic Background of the Sample Study, Problems and perspectives of Self Help Groups, Performance of Self Help Groups and Conclusion. This outstanding Text-cum-Reference book will be of great use to Scholars, Administrators, Planners, Policy-makers, Statesmen and Students of Political Science, Economics, Sociology, Commerce and Women Studites. About The Author:- Dr. G. Sreeramulu, is working as a reader in the post-graduate department of studies and research in Political Science. He obtained M.A. Degree in Political Science in 1988, M. Ed. in 1993, M. Phil in 1994, Doctorate Degree in Education Entitled "Planning and Expenditure on Education during the Plane Period in the State of Karnataka" in 1998 from Bangalore University. The author has also obtained Doctorate Degree in Political Science form Kakatiya University Warangal in 2005. The titled of his thesis is "Public Policy Self Help Groups:- A Case Study of Anantapur District." He has authored highly acclaimed book on 'Planning and Expenditure on Education'. He has participated in several regional, National and International Conferences and presented scholarly papers on various issues concerning social issues, Public Policy Analyisis, Working of Panchayat Raj System, Educational Policies and Expe